Effect of vitamin C supplementation on gingival bleeding - Pribadi, Indra Mustika Setia; Rusminah, Nunung; Rusyanti, Yanti; Suwargiani, Anne Agustina (Padjadjaran Journal of Dentistry, 2018)
Introduction: Periodontitis is a multifactorial disease caused by a disproportion between environmental factors such as periodontal pathogens and the host defence. Genetic factors, hormones, and nutrition may influence host defence mechanisms. One of the nutrition needed for periodontal health is vitamin C. This study was aimed to evaluate the effect of vitamin C supplementation on gingival bleeding. Methods: As much as ninety-eight patients with chronic periodontitis consisted of 42 males and 56 females, aged 30 – 59-years-old participated in this study. Gingival bleeding was assessed before and after 3 months administered with vitamin C supplementation. Gingival bleeding criteria was based on Van der Velden with tooth selection based on Ramfjörd. Result: Gingival bleeding before the administration of vitamin C supplementation was found in the high category at 4 patients (4.1%), medium at 36 patients (36.7%), and low at 58 patients (59.2%).  After 3 months administration of vitamin C supplementation, high category gingival bleeding was found in 2 patients (2%), medium in 16 patients (16.3%), and low in 80 patients (81.6%). Conclusion: There was an effect of vitamin C supplementation on gingival bleeding.Keywords: Chronic periodontitis, vitamin C supplementation, gingival bleeding.